2018
DOI: 10.1016/j.jbiomech.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Aging effects on the Achilles tendon moment arm during walking

Abstract: The Achilles tendon (AT) moment arm transforms triceps surae muscle forces into a moment about the ankle which is critical for functional activities like walking. Moreover, the AT moment arm changes continuously during walking, as it depends on both ankle joint rotation and triceps surae muscle loading (presumably due to bulging of the muscle belly). Here, we posit that aging negatively effects the architecturally complex AT moment arm during walking, which thereby contributes to well-documented reductions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
2
12
1
Order By: Relevance
“…In our study, moment arms were not directly correlated with muscle volumes, body size, or peak plantarflexion torques during walking in either young or older adults. Older adults in our study had slightly smaller moment arms than the young adults, as has been shown previously (Rasske and Franz, 2018 ), though the difference was not significant here.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, moment arms were not directly correlated with muscle volumes, body size, or peak plantarflexion torques during walking in either young or older adults. Older adults in our study had slightly smaller moment arms than the young adults, as has been shown previously (Rasske and Franz, 2018 ), though the difference was not significant here.…”
Section: Discussionsupporting
confidence: 81%
“…Since muscle strength decreases with aging (Narici et al, 2008), individualizing maximal isometric muscle forces in our musculoskeletal models would increase the plantarflexor and hip extensor muscle activations and therefore the plantarflexor and hip extensor muscle energy cost of walking. Furthermore, as reported for the ankle plantarflexors (Rasske and Franz, 2018), it might be that the hip muscle moment arms during walking are smaller in older than in young adults due to smaller three-dimensional shape changes (muscle bulging). However, since the Hill-type muscle models assume constant muscle thickness, this is overlooked in our musculoskeletal models (Zajac, 1989).…”
Section: Discussionmentioning
confidence: 82%
“…Yet, despite those limitations, the UsKin method seems to be most promising for future in vivo studies as it is not limited by range of motion, accounts for inter-individual AT MA differences, and is sensitive to influences of joint rotation and varying contraction intensities. Rightfully so, this ultrasound-based geometric method has emerged to a common approach to determine the dynamic AT MA within recent years 17,[20][21][22][23][24][25]27 . Realistic calculation of TS forces is not only a prerequisite to determine physiological force-length data but also to determine realistic muscle properties including force-velocity relations and elastic properties of muscles from measured external reaction forces or joint torques [51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…(3) A geometric imaging method using motion tracking and ultrasound (UsKin). Thereby, an ultrasound probe (calibrated in space) is used to track the AT line of action [16][17][18][19][20][21][22][23][24][25][26][27] . Similar to the Experimental setup.…”
mentioning
confidence: 99%